Animal Models for the Study of Rodent-Borne Hemorrhagic Fever Viruses: Arenaviruses and Hantaviruses. (21st July 2015) - Golden, Joseph W.; Hammerbeck, Christopher D.; Mucker, Eric M.; Brocato, Rebecca L.
Abstract : Human pathogenic hantaviruses and arenaviruses are maintained in nature by persistent infection of rodent carrier populations. Several members of these virus groups can cause significant disease in humans that is generically termed viral hemorrhagic fever (HF) and is characterized as a febrile illness with an increased propensity to cause acute inflammation. Human interaction with rodent carrier populations leads to infection. Arenaviruses are also viewed as potential biological weapons threat agents. There is an increased interest in studying these viruses in animal models to gain a deeper understating not only of viral pathogenesis, but also for the evaluation of medical countermeasures (MCM) to mitigate disease threats. In this review, we examine current knowledge regarding animal models employed in the study of these viruses. We include analysis of infection models in natural reservoirs and also discuss the impact of strain heterogeneity on the susceptibility of animals to infection. This information should provide a comprehensive reference for those interested in the study of arenaviruses and hantaviruses not only for MCM development but also in the study of viral pathogenesis and the biology of these viruses in their natural reservoirs.